Performing Religious Worship: Discussion around Isese and other religious practice among the Yoruba of West Africa - Julius-Adeoye, Rantimi Jays (Corpus Intellectual, 2024)
Nigeria is the most diversified and populous nation in Africa with more than two hundred million people, and over five hundred ethnic nationalities that practice one religion or the other. Though Nigeria pride itself as secular nation, but many of the unrest and violence in the country are caused by religious intolerance. In fact, there is both a church and mosque in the official residence of the president. In fact, electoral position in the country is conducted on religious line. The most popular religion in the country is Christianity and Islam with prejudice against the indigenous belief system. Therefore, this paper employs ethnography theory to discuss the position of Isese and raise study on the hostility that Christianity and Islam religions visited on the practitioners of the indigenous religions. The paper adopts qualitative research methodology to draw attention to the plight of the adherents of Isese. Among the several Isese festivals celebrated majorly by the Yorubas are Eyo, Igogo. Some of the popular Isese among the Yoruba includes Olojo, Oro, Ogun, Malokun, Egungun, and Sango festivals. The Yoruba with approximately forty million remains the leading ethnic nationalities in the world